Effective stiffness, damping and mass of the body during laboratory simulations of shoulder checks in ice hockey - Aguiar, O. M. G.; Radivojevic, O.; Potvin, B. M.; Vakili, O.; Robinovitch, S. N. (Sports Biomechanics, 2021)
Ice hockey is a fast-paced sport with a high incidence of collisions between players. Shoulder checks are especially common, accounting for a large portion of injuries including concussions. The forces generated during these collisions depend on the inertial and viscoelastic characteristics of the impacting bodies. Furthermore, the effect of shoulder pads in reducing peak force depends on the baseline (unpadded) properties of the shoulder. We conducted experiments with nine men's ice hockey players (aged 19-26) to measure their effective shoulder stiffness, damping and mass during the impact stage of a shoulder check. Participants delivered a style of check commonly observed in men's university ice hockey, involving lateral impact to the deltoid region, with the shoulder brought stationary by the collision. The effective stiffness and damping coefficient of the shoulder averaged 12.8 kN/m and 377N-s/m at 550N, and the effective mass averaged 47% of total body mass. The damping coefficient and stiffness increased with increasing force, but there was no significant difference in the damping coefficient above 350N. Our results provide new evidence on the dynamics of shoulder checks in ice hockey, as a starting point for designing test systems for evaluating and improving the protective value of shoulder pads.